ABOUT CALCULATING THE SUPPORT STRUCTURE OF SMALL OFFSHORE CONCRETE GRAVITY STRUCTURES - Cuong, Dinh Quang (Vietnam Journal of Marine Science and Technology, 2006)
ABOUT CALCULATING THE SUPPORT STRUCTURE OF SMALL OFFSHORE CONCRETE GRAVITY STRUCTURES